Meningkatkan Budaya Organisasi dalam Upaya Meningkatkan Produktivitas Pegawai Yayasan Pendidikan Tajaul Karomah Desa Situ Gadung Kabupaten Tangerang - Aldy, Hafis Laksmana Nur; Budiman, Surya; Irawati, Laila (Jurnal PKM Manajemen Bisnis, 2025)
This community service activity was conducted to address the need for improving organizational culture in order to enhance employee productivity at Yayasan Pendidikan Tajaul Karomah, Desa Situ Gadung, Kabupaten Tangerang. The background of this activity stems from the observation that a weak organizational culture negatively affects employee performance and overall productivity among teachers, staff, and other employees. The primary objective was to strengthen the organizational culture to support increased productivity within the foundation. The activity was held in the auditorium of Yayasan Pendidikan Tajaul Karomah on May 4, 2024, and was facilitated by 12 lecturers from Universitas Pamulang. The participants consisted of 25 teachers, staff, and employees of the foundation. The implementation of the community service involved three phases: planning, execution, and reporting. The methods employed during the activity included material presentations, practical exercises, group discussions, and question-and-answer sessions to ensure active participation and effective knowledge transfer. The results showed a marked improvement in participants’ understanding of organizational culture and its role in enhancing productivity. Participants reported increased motivation and a more cooperative working environment after the activity. These findings indicate that deliberate efforts to develop organizational culture can significantly improve employee productivity in educational institutions.